Nilai Sosial Dalam Novel Home Sweet Loan Karya Almira Bastari - Hakiki, Zikria; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This study aims to describe the social values ​​contained in the novel Home Sweet Loan by Almira Bastari. The focus of the study is directed at the depiction of social values ​​such as social interaction, social conflict, and social change. This study uses a qualitative approach with a descriptive method. The data in this study are in the form of words, sentences, and paragraphs contained in the novel Home Sweet Loan by Almira Bastari and the source of this research data is the novel Home Sweet Loan by Almira Bastari, the third edition in 2023, consisting of 309 pages. The data collection technique in this study is the hermeneutic technique. The data analysis techniques used are coding, classification, analysis and data relationships. The results of the study show that the novel Home Sweet Loan contains social values ​​that reflect the reality of people's lives, especially the younger generation. These values ​​include: 1) social interaction is shown through the relationship between characters and family, partners, and peers. 2) Social conflicts that arise due to differences in values ​​between generations, economic inequality, and the influence of social media. 3) Social changes in community values. The conclusion of this study is that Home Sweet Loan is a reflection of the social dynamics of modern society. This novel presents a realistic portrait of the challenges of life for the younger generation and is a reflective medium for understanding changes in social values ​​and behavior in the digital era.